Assessing the Influence of a Rotating Magnetic Field on Ibuprofen Permeability from Diverse Pharmaceutical Formulations - Anna Nowak; Paula Ossowicz-Rupniewska; Maciej Konopacki; Anna Muzykiewicz-Szymańska; Łukasz Kucharski; Rafał Rakoczy (MDPI AG, 2023)
This study introduces a novel approach for enhancing the transdermal permeability of ibuprofen through the skin by utilising a rotating magnetic field (RMF). The core objective is to systematically evaluate the influence of a 50 Hz RMF on ibuprofen's skin permeability across various formulation types, each employing distinct physical forms and excipients. The experimental setup involved Franz cells with skin as the membrane, exposed to a 50 Hz RMF in conjunction with specific formulations. Subsequent comprehensive analysis revealed a notable increase in the transdermal transport of ibuprofen, irrespective of the formulation employed. Notably, the differences in the initial 30 min of permeation were particularly pronounced. Crucially, this investigation establishes that the application of a 50 Hz RMF resulted in a remarkable over-sevenfold increase in ibuprofen permeability compared to the control group without RMF exposure. It is noteworthy that in all semi-solid pharmaceutical formulations tested, RMF effectively reduced the delay time to zero, underscoring the efficiency of RMF in overcoming barriers to transdermal drug delivery. This research positions the application of RMF as a highly promising and innovative technology, significantly enhancing the transdermal penetration of anti-inflammatory and analgesic drugs through the skin. The demonstrated effectiveness of RMF across diverse formulations suggests its potential in transdermal drug delivery, offering a novel and efficient strategy for improving therapeutic outcomes in the administration of ibuprofen and potentially other pharmaceutical agents.